2011
DOI: 10.1075/pc.19.2.02che
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing sarcasm without language

Henry S. Cheang,
Marc D. Pell

Abstract: The goal of the present research was to determine whether certain speaker intentions conveyed through prosody in an unfamiliar language can be accurately recognized. English and Cantonese utterances expressing sarcasm, sincerity, humorous irony, or neutrality through prosody were presented to English and Cantonese listeners unfamiliar with the other language. Listeners identified the communicative intent of utterances in both languages in a crossed design. Participants successfully identified sarcasm spoken in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…While other cues could be involved in different languages, modulations of mean F0, slower speech rate and longer syllable duration have been consistently shown to be acoustic features used to mark sarcasm or irony in English, French, Italian, German and Cantonese (See Scharrer and Christmann, 2011 for a cross-language review; Rockwell, 2000;Anolli et al 2002;Attardo et al, 2003;Bryant and Fox Tree, 2005;Laval and Bert-Erboul, 2005;Cheang and Pell, 2009;Loevenbruck et al, 2013). Mean F0 has been suggested to be the most important acoustic parameter for marking sarcasm (Cheang and Pell, 2011), but there is evidence that this cue is used differently across languages, research in French and English reporting an increase F0 variability (Attardo et al,2003;Laval and Bert-Erboul, 2005;Loevenbruck et al, 2013) while a study in Cantonese showed a reduced F0 range (Cheang and Pell, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…While other cues could be involved in different languages, modulations of mean F0, slower speech rate and longer syllable duration have been consistently shown to be acoustic features used to mark sarcasm or irony in English, French, Italian, German and Cantonese (See Scharrer and Christmann, 2011 for a cross-language review; Rockwell, 2000;Anolli et al 2002;Attardo et al, 2003;Bryant and Fox Tree, 2005;Laval and Bert-Erboul, 2005;Cheang and Pell, 2009;Loevenbruck et al, 2013). Mean F0 has been suggested to be the most important acoustic parameter for marking sarcasm (Cheang and Pell, 2011), but there is evidence that this cue is used differently across languages, research in French and English reporting an increase F0 variability (Attardo et al,2003;Laval and Bert-Erboul, 2005;Loevenbruck et al, 2013) while a study in Cantonese showed a reduced F0 range (Cheang and Pell, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In view of the prior studies showing that native and foreign users of a language may rely on a set of similar (e.g., Antoniou & Milaki, 2021; Bromberek-Dyzman et al, 2021) or different cues (e.g., Cheang & Pell, 2011; Peters et al, 2016) when making sense of ironic meanings, future studies should verify if the response time and accuracy patterns obtained in this study for advanced Polish users of English would be replicated for different groups of bilinguals, for example, bilinguals with different levels proficiency in their foreign or second languages, and for different tasks. Also, as this study examined student population of Polish users of English, future studies should examine how different age groups of foreign users of English comprehend irony in a selection of tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Next to reading irony for comprehension, English as a foreign language research has also examined irony comprehension when participants were listening to irony. For example, Cheang and Pell (2011) asked native monolingual speakers of English and Cantonese to listen to utterances expressing either sincere or sarcastic remarks, and to judge them for sincerity or ironicity. The results showed that participants succeeded in identifying sarcasm only in their native language, and failed to tell sincerity from sarcasm when they listened to it in the foreign language.…”
Section: Introduction11 Irony Comprehension: Linguistic Competence In...mentioning
confidence: 99%
“…On the other hand, several studies support the existence of acoustic cues that drive recognition of irony without the help of visual, contextual, or semantic cues (e.g., Cheang & Pell, 2008; Woodland & Voyer, 2011), particularly when the material is presented in the listeners’ mother tongue (Cheang & Pell, 2011). Various acoustic cues have been found to be associated with irony (or sarcasm) in different languages.…”
mentioning
confidence: 99%
“…Table 1 summarizes features relative to F0 and its derivatives (i.e., range, minimum, maximum, standard deviation), rate of speech, and dynamics (principally melodic contour). These observations are based on a variety of material, ranging from very controlled (e.g., based on a recognition task involving 32 native speakers of English and Cantonese, only 15% of previously recorded material was retained for use in Cheang & Pell’s 2011 study) to more natural speech (e.g., material from radio broadcasts in Bryant & Fox Tree, 2002, 2005). As illustrated in Table 1, ironic speech is consistently marked by a slower speech rate (or longer duration) across studies.…”
mentioning
confidence: 99%